2020
DOI: 10.1016/j.ijme.2019.100328
|View full text |Cite
|
Sign up to set email alerts
|

Reducing carbon emissions in business through Responsible Management Education: Influence at the micro-, meso- and macro-levels

Abstract: There has long been an understanding that to achieve meaningful progress against sustainability challenges, action is required at multiple levels. With regards to education initiatives, these levels range from macro-level international agreements and activities such as the United Nations Sustainable Development Goals and the United Nations Principles of Responsible Management Education, meso-level influences such as the role of national bodies supporting sustainability in higher education, and micro-level infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 33 publications
0
27
0
3
Order By: Relevance
“…Specifically, Horne, Recker, Michelfelder, Jay, and Kratzer (2020) explore the relation between entrepreneurship and SDGs through a quantitative methodology, whereas Mintrom and Thomas (2018) and Schaltegger, Beckmann, and Hockerts (2018) both published in International Journal of Entrepreneurial Venturing and focus on entrepreneurship to pursue sustainable development, the latter adopting a conceptual approach. The very recent studies by Molthan‐Hill, Robinson, Hope, Dharmasasmita, and McManus (2020) and Nwagwu (2020), published in the International Journal of Management Education , instead focus on responsible management education to pursue SDGs. Molthan‐Hill et al (2020) in particular focus on specific goals: 7 (Affordable and Clean Energy), 13 (Climate Action), and 17 (Partnership to Achieve Goals).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Horne, Recker, Michelfelder, Jay, and Kratzer (2020) explore the relation between entrepreneurship and SDGs through a quantitative methodology, whereas Mintrom and Thomas (2018) and Schaltegger, Beckmann, and Hockerts (2018) both published in International Journal of Entrepreneurial Venturing and focus on entrepreneurship to pursue sustainable development, the latter adopting a conceptual approach. The very recent studies by Molthan‐Hill, Robinson, Hope, Dharmasasmita, and McManus (2020) and Nwagwu (2020), published in the International Journal of Management Education , instead focus on responsible management education to pursue SDGs. Molthan‐Hill et al (2020) in particular focus on specific goals: 7 (Affordable and Clean Energy), 13 (Climate Action), and 17 (Partnership to Achieve Goals).…”
Section: Resultsmentioning
confidence: 99%
“…The very recent studies by Molthan‐Hill, Robinson, Hope, Dharmasasmita, and McManus (2020) and Nwagwu (2020), published in the International Journal of Management Education , instead focus on responsible management education to pursue SDGs. Molthan‐Hill et al (2020) in particular focus on specific goals: 7 (Affordable and Clean Energy), 13 (Climate Action), and 17 (Partnership to Achieve Goals). All the other papers generally deal with the full SDGs set.…”
Section: Resultsmentioning
confidence: 99%
“…Alongside, another study was done by Versteijlen et al (2017) explored the association between online educations in Dutch institutions and concluded that online education results in a significant decrease in the carbon impact of not only the students but also staff members. However, education is important for management staff along with students for proper reduction of CO 2 emission as Molthan-Hill et al (2020) explored micro as well as macro-level educational settings jointly between university students and organizations. Results indicate that this setting reduced CO 2 emission by 507,435 kg in two years and it is recommended to continue it for five years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers question how business education can be a vector of the paradigm shift towards a business (not) as-usual model (Molthan-Hill, Robinson, Hope, Dharmasasmita & McManus, 2020;Borglund, Prenkert, Frostenson, Helin & Du Rietz, 2019;Nwagwu, 2020;Wersun, 2017;Ndubuka & Rey-Marmonier, 2019;de Paula Arruda Filho, 2017;Fougère, Solitander, & Young, 2014), and many initiatives at an international and global level have risen like the Principles for Responsible Management Education (PRME) (Forray & Leigh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity and interconnectedness of Sustainable Development are multi-dimensional (Dyllick & Hockerts, 2002), multi-level (Molthan-Hill et al, 2020), systemic (Bansal, 2002), and multi-stakeholder dependant (Hörisch, Freeman & Schaltegger, 2014), paradoxical (Hahn, Preuss, Pinkse & Figge, 2014). For that, it can not be addressed by isolated and specific theories (Sibbel, 2009), neither from the top of ivory towers, academic silos detached from the outside world (Ralph & Stubbs, 2014).…”
Section: Introductionmentioning
confidence: 99%